Long-term outcomes of surgery for pulmonary artery sling in children†. (31st January 2019) - Yong, Matthew S; Zhu, Michael Z L; Bell, Douglas; Alphonso, Nelson; Brink, Johann; d'Udekem, Yves; Konstantinov, Igor E
Abstract: OBJECTIVES: Pulmonary artery (PA) sling is a rare vascular anomaly often associated with congenital tracheal stenosis. We describe the long-term outcomes with repair of this condition. METHODS: A retrospective study was conducted at 2 institutions. From 1984 to 2018, 33 patients with PA sling underwent repair. RESULTS: The median age at the time of surgery was 5.9 months (quartile 1–3: 2.5–12 months). Concomitant tracheal surgery was required in 21 patients (64%) where slide tracheoplasty was used in 11 patients (52%). There were no early deaths in patients who did not require tracheal surgery ( n = 12). Operative mortality was 22% (2 of 9 patients) between 1984 and 1993, 11% (1 of 9 patients) between 1994 and 2003 and 6.7% (1 of 15 patients) between 2004 and 2018. The 15-year probability of survival for patients who had PA sling repair alone was 100%, and for patients who required PA sling and tracheal repair was 76 ± 10% (95% confidence interval 51–89%) ( P = 0.08). The mean follow-up for survivors was 14 ± 9.8 years (3 months–33 years). All survivors were in the New York Heart Association functional class I/II at the last follow-up. Spirometry performed at a median age of 10.4 years after PA sling and tracheal surgery demonstrated obstructive lung defects with median forced expiratory volume in 1 s of 1.0 l (48% predicted), forced vital capacity of 1.5 l (74% predicted) and forced expiratory volume in 1 s/forced vital capacity of 0.69 (78% predicted). CONCLUSIONS: Early mortality after PA sling repair is determined by the need for tracheal surgery. Though late survival was excellent, and the majority of survivors remained asymptomatic, long-term respiratory assessment and follow-up is warranted for these patients.